The Correlation Between Family Roles and Hypertension Control in The Working Area of Rogotrunan Public Health Center, Lumajang - Agustin Izza Afkarina; Marfuah; Rizka Yunita (Health and Technology Journal (HTechJ), 2024)
Hypertension is one of the non-communicable cardiovascular diseases that many people suffer from, with a significant increase in prevalence with increasing age. Rogotrunan Lumajang Health Center is one of the health centers located in Lumajang Regency with the highest number of hypertension sufferers in Lumajang. Hypertension sufferers can experience sudden death because hypertension is the silent killer and the silent disease. Hypertension sufferers need a support system from the family to control their blood pressure and avoid conditions getting worse and avoid complications due to hypertension. The role of the family is very necessary for hypertension sufferers over a long period of time and continuously. The family roles needed to achieve optimal health include the  role of the family as encouragement, initiator, coordinator, motivator and educator. The research design used correlation analytic, using a cross sectional approach, the study population was all hypertensive patients in the working area of the Rogotrunan Lumajang Community Health Center, namely 185 patients, using a simple random sampling technique. The research sample was 126 patients. The statistical test uses Spearman rank with a significance level of 0.05. The research results showed that 109 respondents had a good family role (86.5%), and 99 respondents had very good hypertension control (78.6%). After carrying out the Spearman Rank statistical test, the Sig value was obtained. (2-tailed) results at a significant level of 0.000 < 0.05, meaning there is a correlation the role of the family and controlling hypertension in the working area of the Rogotrunan Lumajang Community Health Center with the level of closeness of the correlation showing a value of 0.405 in  the Moderate/Fair category. It is hoped that families will be able to play their role with family members who experience hypertension in controlling hypertension to prevent recurrence of hypertension.